Motives for using social media among post-basic education students (11-12) in Al-Buraimi Governorate schools in the Sultanate of Oman - Alkhawaja, Abdelfattah Mohammed Said; Albalushi, Shahin Mohammed Ali Kamal (Journal of Educational and Psychological Sciences, 2020)
The main of this study is to identify the motivation for using social media among grade (11-12) school students at Al-Buraimi governorate in Oman through the following variables (class, gender, time, type of media mostly visited & the purpose of using the site). Among sample (240 male & female) students, who were distributed into 13 different schools from Al-Buraimi, mahdah & as-sunaynah. A questionnaire of motivation for using Social Media has been used. The sample percentage was 13% of the whole population target. The results showed that there are no statistical differences between grade 11 and grade 12 students in using social media. In addition, there is no significant difference in (gender) in using social media. Also, the study revealed that the most highlighted usage of social media amongst the study sample was for exploring the public culture. While the results showed that the number (155) of the study sample, which means (60%), they are using social media according to the available conditions. (47.9%) percentage of the sample was on social media about (1-3 hours). The most popular site was Instagram. The study recommended activating the role of the school administration, teacher & social worker in the school for helping students to take the benefit from social media & address the negative aspects of these means through school radio, lectures, seminars, scientific journals & etc.